Preparation method of water electrolysis hydrogen production catalyst with efficient mass transfer three-phase interface
By synthesizing zinc-based metal organic frameworks on the surface of molybdenum disulfide nanosheets and combining them with dopamine-modified graphene oxide and other materials to form layered materials, the problem of the reduction of catalytic active sites caused by the metastasis of platinum atoms in the catalyst is solved, and the catalytic reaction efficiency and hydrogen production efficiency of electrolytic water hydrogen production catalyst are improved.
Patent Information
- Application Number
- CN202510053088.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The displacement of platinum atoms in the catalyst leads to a decrease in the number of catalytic active sites and low catalytic reaction efficiency, which affects the catalytic performance of the electrolytic water hydrogen production catalyst.
By synthesizing a zinc-based metal organic framework on the surface of molybdenum disulfide nanosheets, pretreated molybdenum disulfide nanosheets are formed, and combined with dopamine-modified graphene oxide, polyethylene glycol and composite materials to form a layered material, improving the number of active sites and electron transport properties of the catalyst.
The catalytic reaction efficiency of the electrolytic water hydrogen production catalyst is improved, the catalytic reaction time is shortened, the hydrogen production efficiency is enhanced, and the service life of the catalyst is extended.
Smart Images

Figure BDA0005240553250000181
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode catalysts for hydrogen, and in particular to a method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface. Background Art
[0002] Hydrogen energy is considered to be an important carrier for building a "multi-energy complementary" energy supply system. The use of nickel wire mesh electrodes to produce hydrogen has high electrochemical reaction activity and good mass transfer performance, which can significantly improve the reaction rate and efficiency of hydrogen production. By spraying the water electrolysis hydrogen production catalyst on the nickel wire mesh electrode, it is used as an electrolyzer hydrogen production catalyst with a high hydrogen production efficiency. Among them, the water electrolysis hydrogen production catalyst is used to accelerate the reaction rate of hydrogen and generate current, such as catalysts, nickel metal, etc.
[0003] The catalyst is a carrier catalyst in which platinum metal is loaded onto activated carbon. When adsorbing oxygen intermediates, platinum atoms are easily displaced and detached from the catalyst, resulting in a decrease in the number of catalytic active sites, affecting the catalytic activity of the catalyst; small-sized catalyst particles are prone to agglomeration and deactivation, affecting the catalytic performance of the catalyst for hydrogen production by electrolysis of water, and the catalytic reaction efficiency of the catalyst is low, and the catalytic reaction time is too long, affecting the hydrogen production efficiency of the electrolyzer hydrogen production catalyst. Summary of the invention
[0004] The present invention provides a method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface, which solves the problem that platinum atoms in the catalyst are easily displaced, resulting in a decrease in the number of catalytic active sites and low catalytic reaction efficiency.
[0005] The technical solution of the present invention:
[0006] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0007] S1. Mix the catalyst and the mixed acid, stir at 45-55 ° C for 4-6 hours, filter and dry to obtain a pretreated catalyst;
[0008] S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 300-400 r / min for 20-30 min, filtered, washed, and dried to obtain a modified catalyst;
[0009] S3. The modified catalyst, polyethylene glycol and the composite material are added to ethanol, stirred at 70-80 ° C for 30-40 min, ultrasonically treated at 40-60 KHz for 5-15 min, filtered, washed and dried to obtain a composite catalyst;
[0010] S4. Add the composite catalyst, cellulose and cross-linking agent into ethanol, mix, stir and react at 30-40° C. for 20-30 min, and freeze-dry to obtain a water electrolysis hydrogen production catalyst.
[0011] The composite material is obtained by mixing modified molybdenum disulfide nanosheets and 4,4'-dinonyl-2,2'-bipyridine;
[0012] The modified molybdenum disulfide nanosheet is obtained by mixing and reacting the molybdenum disulfide nanosheet with zinc nitrate hexahydrate and dimethylimidazole, and then mixing and reacting the molybdenum disulfide nanosheet with cerium nitrate and ammonia water.
[0013] Furthermore, during the reaction process of step S1, the mixed acid formed by the aqueous sulfuric acid solution and the aqueous nitric acid solution has strong oxidizing properties and can undergo oxidation reaction with the oxygen-containing functional groups on the surface of the carbon carrier in the catalyst, thereby forming a large number of carboxyl groups on the catalyst surface.
[0014] Furthermore, during the reaction process of step S2, the surface of the pretreated catalyst contains a large number of carboxyl groups, which can be chemically bonded to the phenolic hydroxyl groups on the surface of the dopamine-modified graphene oxide, so that the pretreated catalyst is deposited on the surface of the dopamine-modified graphene oxide.
[0015] Furthermore, during the reaction process of step S3 above, polyethylene glycol is used as a linker, and its molecular chain can be inserted between the modified catalyst and the composite material, and the hydroxyl groups contained in the polyethylene glycol molecular chain can be chemically bonded to the oxygen-containing functional groups on the surface of the modified catalyst and the composite material, so that the modified catalyst and the composite material are stacked on each other to form a layered material, i.e., a composite catalyst.
[0016] Furthermore, during the reaction process of step S4, cellulose can be combined with the cross-linking agent epichlorohydrin through chemical bonds to form an aerogel with a cross-linked network structure, and the modified catalyst can be embedded in the aerogel to form a catalyst for hydrogen production by electrolysis of water.
[0017] Furthermore, in step S1, the ratio of the catalyst to the mixed acid is (8-10) g: (60-70) mL.
[0018] Furthermore, in step S1, the mixed acid is prepared by mixing an aqueous sulfuric acid solution and an aqueous nitric acid solution in a volume ratio of (40-50):(10-20).
[0019] Furthermore, the mass fraction of the aqueous sulfuric acid solution is 70-80%; the mass fraction of the aqueous nitric acid solution is 68-72%.
[0020] Furthermore, in step S2, the ratio of the pretreatment catalyst, dopamine-modified graphene oxide and ethanol is (2.3-2.5) g: (3.2-3.4) g: (45-55) mL.
[0021] Furthermore, in step S3, the ratio of the modified catalyst, polyethylene glycol, composite material and ethanol is (3-4) g: (1-2) g: (4-5) g: (80-120) mL.
[0022] Furthermore, in step S4, the ratio of the composite catalyst, cellulose, cross-linking agent and ethanol is (2-3) g: (4-5) g: (0.4-0.6) mL: (70-90) mL.
[0023] Furthermore, the cross-linking agent is epichlorohydrin.
[0024] Further, the composite material is prepared by the following steps:
[0025] A1. Add molybdenum disulfide nanosheets to deionized water, stir evenly, add zinc nitrate hexahydrate and 2-methylimidazole, stir and react at 30-40°C for 1-3h, let stand overnight, filter, wash, place in tert-butanol, stir, take out, and freeze-dry to obtain pretreated molybdenum disulfide nanosheets;
[0026] A2. Add cerium nitrate to ethanol and deionized water, stir evenly, add pretreated molybdenum disulfide nanosheets and ammonia water, stir and react at 60-70 ° C for 2-3 hours, cool to room temperature, remove, wash, dry, calcine at 280-320 ° C for 1-3 hours, cool to room temperature to obtain modified molybdenum disulfide nanosheets;
[0027] A3. Add 4,4'-dinonyl-2,2'-bipyridine to dichloromethane, stir evenly, add modified molybdenum disulfide nanosheets, stir at a speed of 100-200 rpm for 1-2 hours, heat at 35-45°C for 25-35 minutes, reduce pressure and evacuate, filter, and dry to obtain a composite material.
[0028] Furthermore, during the above-mentioned reaction A1, the hydroxyl groups contained on the surface of the molybdenum disulfide nanosheets can combine with the zinc ions in the zinc nitrate hexahydrate, so that the zinc ions are deposited on the surface of the molybdenum disulfide nanosheets, and the zinc ions, as the central metal ions, can also react with the nitrogen atoms in the dimethylimidazole to form a coordination bond, so that the nitrogen atoms of the 2-methylimidazole act as ligands and combine with the zinc ions in the form of coordination bonds to form crystals. As the reaction proceeds, a porous zinc-based metal organic skeleton is formed, thereby realizing the synthesis of the zinc-based metal organic skeleton on the surface of the molybdenum disulfide nanosheets to form pretreated molybdenum disulfide nanosheets.
[0029] Furthermore, in the above-mentioned A2 reaction process, the porous structure on the surface of the pretreated molybdenum disulfide nanosheet has good adsorption performance, and can adsorb cerium nitrate and ammonia water onto the surface of the molybdenum disulfide nanosheet, and the cerium ions in the cerium nitrate can combine with the hydroxide ions provided by the ammonia water to form hydroxide on the surface of the molybdenum disulfide nanosheet. After calcination at 280-320°C, the hydroxide decomposes by heat to form nano-cerium oxide on the surface of the pretreated molybdenum disulfide nanosheet, thereby obtaining modified molybdenum disulfide nanosheet.
[0030] Furthermore, during the above reaction process A3, 4,4'-dinonyl-2,2'-bipyridine is dissolved in dichloromethane to form a solution. Under a negative pressure of -0.05 MPa, the formed solution can be adsorbed into the pores on the surface of the modified molybdenum disulfide nanosheets to form a composite material.
[0031] Furthermore, in step A1, the molybdenum disulfide nanosheets, deionized water, zinc nitrate hexahydrate and 2-methylimidazole are used in a ratio of (6-7) g: (55-65) mL: (1-2) g: (5-6) g.
[0032] Furthermore, in step A2, the ratio of the cerium nitrate, ethanol, deionized water, pretreated molybdenum disulfide nanosheets and ammonia water is (2-3) g: (15-25) mL: (15-25) mL: (3-4) g: (1-2) mL.
[0033] Furthermore, in step A3, the ratio of the amount of 4,4'-dinonyl-2,2'-bipyridine, dichloromethane and modified molybdenum disulfide nanosheets is (2-4) g: (45-55) mL: (5-7) g.
[0034] Furthermore, dopamine-modified graphene oxide is prepared by the following steps:
[0035] The graphene oxide is added into Tris-HCl buffer, stirred evenly, dopamine is added, stirred for reaction, filtered, washed and dried to obtain dopamine-modified graphene oxide.
[0036] Furthermore, in Tris-HCl buffer, dopamine can self-polymerize on the surface of graphene oxide to form polydopamine, so that the surface of graphene oxide contains a large number of phenolic hydroxyl groups and has good adhesion properties, which is conducive to the attachment of the pretreated catalyst to the dopamine-modified graphene oxide surface.
[0037] Furthermore, the ratio of graphene oxide, Tris-HCl buffer and dopamine is (2-3) g:(35-45) mL:(0.4-0.6) g.
[0038] The present invention has the following beneficial effects:
[0039] (1) In the technical solution of the present invention, a zinc-based metal organic framework is synthesized on the surface of a molybdenum disulfide nanosheet to form a pretreated molybdenum disulfide nanosheet. The molybdenum disulfide nanosheet serves as a carrier and has a large specific surface area, and can load a large amount of porous zinc-based metal organic framework. The porous structure of the zinc-based metal organic framework can increase the active sites of the water electrolysis hydrogen production catalyst, improve the catalytic reaction efficiency of the catalyst, shorten the catalytic reaction time, and improve the hydrogen production efficiency. In addition, the molybdenum disulfide nanosheet has efficient electron transport performance and improves the electrochemical performance.
[0040] (2) In the technical solution of the present invention, nano-cerium oxide is formed on the surface of pretreated molybdenum disulfide nanosheets. On the one hand, the nano-cerium oxide forms a concave-convex structure on the surface of the pretreated molybdenum disulfide nanosheets, which can enhance the ionic conductivity and thus the electrochemical performance of the battery. On the other hand, the nano-cerium oxide can promote the electrochemical reaction of hydrogen on the water electrolysis hydrogen production catalyst, thereby improving the output power and energy density of the battery. In addition, the formation of the nano-cerium oxide on the surface of the pretreated molybdenum disulfide nanosheets forms a concave-convex layer, which increases the contact area between the water electrolysis hydrogen production catalyst and the reactants, thereby further improving the catalytic performance of the water electrolysis hydrogen production catalyst.
[0041] (3) In the technical scheme of the present invention, the nitrogen element contained in 4,4'-dinonyl-2,2'-bipyridine has good adsorption performance for platinum atoms, and can adsorb and fix the platinum atoms that are displaced and separated from the catalyst during use, thereby avoiding the precipitation of platinum atoms, which leads to a decrease in the catalytic performance of the water electrolysis hydrogen production catalyst. 4,4'-dinonyl-2,2'-bipyridine is adsorbed into the holes on the surface of the modified molybdenum disulfide nanosheets, so that the modified molybdenum disulfide nanosheets have the effect of adsorbing and fixing the platinum atoms in the catalyst, and 4,4'-dinonyl-2,2'-bipyridine is compounded with the porous material on the surface of the modified molybdenum disulfide nanosheets to increase the adsorption capacity of platinum atoms. In addition, the detached platinum atoms are adsorbed into the pores in the modified molybdenum disulfide nanosheets, which can continue to exert the catalytic performance of the water electrolysis hydrogen production catalyst, thereby increasing the service life of the water electrolysis hydrogen production catalyst.
[0042] (4) In the technical solution of the present invention, dopamine-modified graphene oxide is used as a carrier of the pretreatment catalyst to increase the number of catalytic active sites, thereby improving the rate and efficiency of the catalytic reaction, and can effectively disperse the catalyst to prevent its agglomeration and deactivation, so that the catalyst can be more fully in contact with the reactants, thereby improving the catalyst of the water electrolysis hydrogen production catalyst.
[0043] (5) In the technical solution of the present invention, the modified catalyst and the composite material are stacked on each other to form a layered material. The reactants can penetrate into the sandwich structure, providing more reaction sites, effectively reducing the activation energy of the hydrogen-oxygen reaction, and allowing the reaction to proceed smoothly at a lower temperature and pressure. The formed layered material can also adsorb and fix the platinum atoms that are displaced and separated from the catalyst during use, thereby avoiding the precipitation of platinum atoms and improving the catalytic activity of the water electrolysis hydrogen production catalyst; the water electrolysis hydrogen production catalyst exists in the form of aerogel, and has the functions of high electrochemical active area and durability. DETAILED DESCRIPTION
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0046] Wherein, the cross-linking agent is epichlorohydrin;
[0047] The particle size of molybdenum disulfide nanosheets is 0.2μm, Zhejiang Yamei Nano Technology Co., Ltd.
[0048] The particle size of graphene oxide is 0.5 μm, Hubei Langbowan Biomedicine Co., Ltd.
[0049] Catalyst, Shanghai Hesen Electric Co., Ltd.
[0050] Example 1
[0051] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0052] S1. The catalyst was mixed with the mixed acid, stirred at 45°C for 4h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0053] The ratio of catalyst to mixed acid is 8 g:60 mL;
[0054] The mixed acid is prepared by mixing a sulfuric acid aqueous solution with a mass fraction of 70% and a nitric acid aqueous solution with a mass fraction of 68% in a volume ratio of 40:10;
[0055] S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 300 r / min for 20 min, filtered, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain a modified catalyst;
[0056] The ratio of pretreated catalyst, dopamine-modified graphene oxide and ethanol was 2.3 g:3.2 g:45 mL;
[0057] S3. The modified catalyst, polyethylene glycol and the composite material were added to ethanol, stirred at 70°C for 30 min, ultrasonically treated at 40 KHz for 5 min, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain a composite catalyst;
[0058] The ratio of modified catalyst, polyethylene glycol, composite material and ethanol is 3g:1g:4g:80mL;
[0059] S4. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 30°C for 20 minutes, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0060] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 2g:4g:0.4mL:70mL.
[0061] The composite material is prepared by the following steps:
[0062] A1. 6 g of molybdenum disulfide nanosheets were added to 55 mL of deionized water, stirred evenly, 1 g of zinc nitrate hexahydrate and 5 g of 2-methylimidazole were added, stirred at 30 ° C for 1 hour, and then allowed to stand overnight. The mixture was filtered, washed with deionized water 3 times, placed in 30 mL of tert-butanol to replace the water, taken out, and freeze-dried at -20 ° C for 1 hour to obtain pretreated molybdenum disulfide nanosheets;
[0063] A2. Add 2 g of cerium nitrate to 15 mL of ethanol and 15 mL of deionized water, stir evenly, add 3 g of pretreated molybdenum disulfide nanosheets and 1 mL of 13 mol / L ammonia water, stir and react at 60 ° C for 2 h, cool to room temperature, take out, wash 3 times with ethanol, wash 3 times with deionized water, dry in an oven at 80 ° C for 30 min, calcine at 280 ° C for 1 h, cool to room temperature, and obtain modified molybdenum disulfide nanosheets;
[0064] A3. Add 2 g of 4,4'-dinonyl-2,2'-bipyridine to 45 mL of dichloromethane, stir evenly, add 5 g of modified molybdenum disulfide nanosheets, place on a rotary evaporator, stir at 100 rpm for 1 hour, heat in a 40°C water bath for 30 minutes, reduce pressure and evacuate to -0.05 MPa, filter, and dry in an oven at 50°C for 30 minutes to obtain a composite material.
[0065] Dopamine modified graphene oxide is specifically prepared by the following steps:
[0066] 2 g of graphene oxide was added to 35 mL of Tris-HCl buffer with a pH of 8.5, stirred evenly, 0.4 g of dopamine was added, stirred and reacted for 2 h, filtered, washed with deionized water 3 times, and dried at room temperature to obtain dopamine-modified graphene oxide.
[0067] Example 2
[0068] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0069] S1. The catalyst was mixed with a mixed acid, stirred at 50°C for 5h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0070] The ratio of catalyst to mixed acid is 9 g:65 mL;
[0071] The mixed acid is prepared by mixing a 75% by mass aqueous sulfuric acid solution and a 70% by mass aqueous nitric acid solution in a volume ratio of 45:15;
[0072] S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 350 r / min for 25 min, filtered, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain a modified catalyst;
[0073] The ratio of pretreated catalyst, dopamine-modified graphene oxide and ethanol was 2.4 g:3.3 g:50 mL;
[0074] S3. The modified catalyst, polyethylene glycol and the composite material were added to ethanol, stirred at 75°C for 35 minutes, ultrasonically treated at 50KHz for 10 minutes, filtered, washed with deionized water three times, and dried in an oven at 70°C for 10 minutes to obtain a composite catalyst;
[0075] The ratio of modified catalyst, polyethylene glycol, composite material and ethanol is 3.5 g:1.5 g:4.5 g:100 mL;
[0076] S4. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 35°C for 25 minutes, continue stirring to form a gel, filter, wash with deionized water three times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0077] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 2.5g:4.5g:0.5mL:80mL.
[0078] The composite material is prepared by the following steps:
[0079] A1. Add 6.5 g of molybdenum disulfide nanosheets to 60 mL of deionized water, stir evenly, add 1.5 g of zinc nitrate hexahydrate and 5.5 g of 2-methylimidazole, stir and react at 35 ° C for 2 h, let stand overnight, filter, wash with deionized water 3 times, place in 30 mL of tert-butanol to replace the water, take out, freeze-dry at -20 ° C for 1 h to obtain pretreated molybdenum disulfide nanosheets;
[0080] A2. Add 2.5 g of cerium nitrate to 20 mL of ethanol and 20 mL of deionized water, stir evenly, add 3.5 g of pretreated molybdenum disulfide nanosheets and 1.5 mL of 13 mol / L ammonia water, stir and react at 65 ° C for 2.5 h, cool to room temperature, take out, wash 3 times with ethanol, wash 3 times with deionized water, dry in an oven at 80 ° C for 30 min, calcine at 300 ° C for 2 h, and cool to room temperature to obtain modified molybdenum disulfide nanosheets;
[0081] A3. Add 3 g of 4,4'-dinonyl-2,2'-bipyridine to 50 mL of dichloromethane, stir evenly, add 6 g of modified molybdenum disulfide nanosheets, place on a rotary evaporator, stir at 150 rpm for 1.5 h, heat in a 40°C water bath for 30 min, reduce pressure and evacuate to -0.05 MPa, filter, and dry in an oven at 50°C for 30 min to obtain a composite material.
[0082] Dopamine modified graphene oxide is specifically prepared by the following steps:
[0083] 2.5 g of graphene oxide was added to 40 mL of Tris-HCl buffer with a pH of 8.5, stirred evenly, 0.5 g of dopamine was added, stirred and reacted for 2 h, filtered, washed with deionized water 3 times, and dried at room temperature to obtain dopamine-modified graphene oxide.
[0084] Example 3
[0085] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0086] S1. The catalyst was mixed with the mixed acid, stirred at 55°C for 6h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0087] The ratio of catalyst to mixed acid is 10 g:70 mL;
[0088] The mixed acid is prepared by mixing an aqueous solution of sulfuric acid having a mass fraction of 80% and an aqueous solution of nitric acid having a mass fraction of 72% in a volume ratio of 50:20;
[0089] S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 400 r / min for 30 min, filtered, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain a modified catalyst;
[0090] The ratio of pretreated catalyst, dopamine-modified graphene oxide and ethanol was 2.5 g:3.4 g:55 mL;
[0091] S3. The modified catalyst, polyethylene glycol and the composite material were added to ethanol, stirred at 80°C for 40 min, ultrasonically treated at 60 KHz for 15 min, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain a composite catalyst;
[0092] The ratio of the composite catalyst, polyethylene glycol, composite material and ethanol is 4g:2g:5g:120mL;
[0093] S4. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 40°C for 30 minutes, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0094] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 3g:5g:0.6mL:90mL.
[0095] The composite material is prepared by the following steps:
[0096] A1. 7 g of molybdenum disulfide nanosheets were added to 65 mL of deionized water, stirred evenly, and 2 g of zinc nitrate hexahydrate and 6 g of 2-methylimidazole were added. After stirring at 40 ° C for 3 h, the mixture was allowed to stand overnight, filtered, washed with deionized water 3 times, placed in 30 mL of tert-butanol to replace the water, taken out, and freeze-dried at -20 ° C for 1 h to obtain pretreated molybdenum disulfide nanosheets;
[0097] A2. Add 3 g of cerium nitrate to 25 mL of ethanol and 25 mL of deionized water, stir evenly, add 4 g of pretreated molybdenum disulfide nanosheets and 21.5 mL of 13 mol / L ammonia water, stir and react at 70 ° C for 3 h, cool to room temperature, take out, wash 3 times with ethanol, wash 3 times with deionized water, dry in an oven at 80 ° C for 30 min, calcine at 320 ° C for 3 h, cool to room temperature, and obtain modified molybdenum disulfide nanosheets;
[0098] A3. Add 4 g of 4,4'-dinonyl-2,2'-bipyridine to 55 mL of dichloromethane, stir evenly, add 7 g of modified molybdenum disulfide nanosheets, place on a rotary evaporator, stir at 200 rpm for 2 hours, heat in a 45°C water bath for 35 minutes, reduce pressure and evacuate to -0.05 MPa, filter, and dry in an oven at 50°C for 30 minutes to obtain a composite material.
[0099] Dopamine modified graphene oxide is specifically prepared by the following steps:
[0100] 3 g of graphene oxide was added to 45 mL of Tris-HCl buffer with a pH of 8.5, stirred evenly, 0.6 g of dopamine was added, stirred and reacted for 2 h, filtered, washed with deionized water 3 times, and dried at room temperature to obtain dopamine-modified graphene oxide.
[0101] Comparative Example 1
[0102] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0103] S1. The catalyst was mixed with the mixed acid, stirred at 55°C for 6h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0104] The ratio of catalyst to mixed acid is 10 g:70 mL;
[0105] The mixed acid is prepared by mixing an aqueous solution of sulfuric acid having a mass fraction of 80% and an aqueous solution of nitric acid having a mass fraction of 72% in a volume ratio of 50:20;
[0106] S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 400 r / min for 30 min, filtered, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain a modified catalyst;
[0107] The ratio of pretreated catalyst, dopamine-modified graphene oxide and ethanol was 2.5 g:3.4 g:55 mL;
[0108] S3. The modified catalyst, polyethylene glycol and the composite material were added to ethanol, stirred at 80°C for 40 min, ultrasonically treated at 60 KHz for 15 min, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain a composite catalyst;
[0109] The ratio of modified catalyst, polyethylene glycol, composite material and ethanol is 4g:2g:5g:120mL;
[0110] S4. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 40°C for 30 minutes, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0111] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 3g:5g:0.6mL:90mL.
[0112] The composite material is prepared by the following steps:
[0113] A1. Add 3g of cerium nitrate to 25mL of ethanol and 25mL of deionized water, stir evenly, add 4g of molybdenum disulfide nanosheets and 21.5mL of 13mol / L ammonia water, stir and react at 70°C for 3h, cool to room temperature, take out, wash with ethanol 3 times, wash with deionized water 3 times, dry in an oven at 80°C for 30min, calcine at 320°C for 3h, cool to room temperature to obtain modified molybdenum disulfide nanosheets;
[0114] A2. Add 4 g of 4,4'-dinonyl-2,2'-bipyridine to 55 mL of dichloromethane, stir evenly, add 7 g of modified molybdenum disulfide nanosheets, place on a rotary evaporator, stir at 200 rpm for 2 hours, heat in a 45°C water bath for 35 minutes, reduce pressure and evacuate to -0.05 MPa, filter, and dry in an oven at 50°C for 30 minutes to obtain a composite material.
[0115] Dopamine modified graphene oxide is specifically prepared by the following steps:
[0116] 3 g of graphene oxide was added to 45 mL of Tris-HCl buffer with a pH of 8.5, stirred evenly, 0.6 g of dopamine was added, stirred and reacted for 2 h, filtered, washed with deionized water 3 times, and dried at room temperature to obtain dopamine-modified graphene oxide.
[0117] Comparative Example 2
[0118] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0119] S1. The catalyst was mixed with the mixed acid, stirred at 55°C for 6h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0120] The ratio of catalyst to mixed acid is 10 g:70 mL;
[0121] The mixed acid is prepared by mixing an aqueous solution of sulfuric acid having a mass fraction of 80% and an aqueous solution of nitric acid having a mass fraction of 72% in a volume ratio of 50:20;
[0122] S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 400 r / min for 30 min, filtered, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain a modified catalyst;
[0123] The ratio of pretreated catalyst, dopamine-modified graphene oxide and ethanol was 2.5 g:3.4 g:55 mL;
[0124] S3. The modified catalyst, polyethylene glycol and the composite material were added to ethanol, stirred at 80°C for 40 min, ultrasonically treated at 60 KHz for 15 min, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain a composite catalyst;
[0125] The ratio of modified catalyst, polyethylene glycol, composite material and ethanol is 4g:2g:5g:120mL;
[0126] S4. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 40°C for 30 minutes, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0127] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 3g:5g:0.6mL:90mL.
[0128] The composite material is prepared by the following steps:
[0129] A1. 7 g of molybdenum disulfide nanosheets were added to 65 mL of deionized water, stirred evenly, and 2 g of zinc nitrate hexahydrate and 6 g of 2-methylimidazole were added. After stirring at 40 ° C for 3 h, the mixture was allowed to stand overnight, filtered, washed with deionized water 3 times, placed in 30 mL of tert-butanol to replace the water, taken out, and freeze-dried at -20 ° C for 1 h to obtain pretreated molybdenum disulfide nanosheets;
[0130] A2. Add 4 g of 4,4'-dinonyl-2,2'-bipyridine to 55 mL of dichloromethane, stir evenly, add 7 g of pretreated molybdenum disulfide nanosheets, place on a rotary evaporator, stir at 200 rpm for 2 hours, heat in a 45°C water bath for 35 minutes, reduce pressure and evacuate to -0.05 MPa, filter, and dry in an oven at 50°C for 30 minutes to obtain a composite material.
[0131] Dopamine modified graphene oxide is specifically prepared by the following steps:
[0132] 3 g of graphene oxide was added to 45 mL of Tris-HCl buffer with a pH of 8.5, stirred evenly, 0.6 g of dopamine was added, stirred and reacted for 2 h, filtered, washed with deionized water 3 times, and dried at room temperature to obtain dopamine-modified graphene oxide.
[0133] Comparative Example 3
[0134] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0135] S1. The catalyst was mixed with the mixed acid, stirred at 55°C for 6h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0136] The ratio of catalyst to mixed acid is 10 g:70 mL;
[0137] The mixed acid is prepared by mixing an aqueous solution of sulfuric acid having a mass fraction of 80% and an aqueous solution of nitric acid having a mass fraction of 72% in a volume ratio of 50:20;
[0138] S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 400 r / min for 30 min, filtered, washed with deionized water three times, and dried in an oven at 70° C. for 10 min to obtain a modified catalyst;
[0139] The ratio of pretreated catalyst, dopamine-modified graphene oxide and ethanol was 2.5 g:3.4 g:55 mL;
[0140] S3. The modified catalyst, polyethylene glycol and the composite material were added to ethanol, stirred at 80°C for 40 min, ultrasonically treated at 60 KHz for 15 min, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain a composite catalyst;
[0141] The ratio of modified catalyst, polyethylene glycol, composite material and ethanol is 4g:2g:5g:120mL;
[0142] S4. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 40°C for 30 minutes, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0143] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 3g:5g:0.6mL:90mL.
[0144] The composite material is prepared by the following steps:
[0145] A1. 7 g of molybdenum disulfide nanosheets were added to 65 mL of deionized water, stirred evenly, and 2 g of zinc nitrate hexahydrate and 6 g of 2-methylimidazole were added. After stirring at 40 ° C for 3 h, the mixture was allowed to stand overnight, filtered, washed with deionized water 3 times, placed in 30 mL of tert-butanol to replace the water, taken out, and freeze-dried at -20 ° C for 1 h to obtain pretreated molybdenum disulfide nanosheets;
[0146] A2. Add 3 g of cerium nitrate to 25 mL of ethanol and 25 mL of deionized water, stir evenly, add 4 g of pretreated molybdenum disulfide nanosheets and 21.5 mL of 13 mol / L ammonia water, stir and react at 70 ° C for 3 h, cool to room temperature, take out, wash 3 times with ethanol, wash 3 times with deionized water, dry in an oven at 80 ° C for 30 min, calcine at 320 ° C for 3 h, cool to room temperature, and obtain a composite material.
[0147] Dopamine modified graphene oxide is specifically prepared by the following steps:
[0148] 3 g of graphene oxide was added to 45 mL of Tris-HCl buffer with a pH of 8.5, stirred evenly, 0.6 g of dopamine was added, stirred and reacted for 2 h, filtered, washed with deionized water 3 times, and dried at room temperature to obtain dopamine-modified graphene oxide.
[0149] Comparative Example 4
[0150] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0151] S1. The catalyst was mixed with the mixed acid, stirred at 55°C for 6h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0152] The ratio of catalyst to mixed acid is 10 g:70 mL;
[0153] The mixed acid is prepared by mixing an aqueous solution of sulfuric acid having a mass fraction of 80% and an aqueous solution of nitric acid having a mass fraction of 72% in a volume ratio of 50:20;
[0154] S2. The pretreated catalyst and graphene oxide were added to ethanol, stirred at 400 r / min for 30 min, filtered, washed with deionized water three times, and dried in an oven at 70 ° C for 10 min to obtain a modified catalyst;
[0155] The ratio of pretreated catalyst, graphene oxide and ethanol was 2.5 g:3.4 g:55 mL;
[0156] S3. The modified catalyst, polyethylene glycol and the composite material were added to ethanol, stirred at 80°C for 40 min, ultrasonically treated at 60 KHz for 15 min, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain a composite catalyst;
[0157] The ratio of modified catalyst, polyethylene glycol, composite material and ethanol is 4g:2g:5g:120mL;
[0158] S4. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 40°C for 30 minutes, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0159] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 3g:5g:0.6mL:90mL.
[0160] The composite material is prepared by the following steps:
[0161] A1. 7 g of molybdenum disulfide nanosheets were added to 65 mL of deionized water, stirred evenly, and 2 g of zinc nitrate hexahydrate and 6 g of 2-methylimidazole were added. After stirring at 40 ° C for 3 h, the mixture was allowed to stand overnight, filtered, washed with deionized water 3 times, placed in 30 mL of tert-butanol to replace the water, taken out, and freeze-dried at -20 ° C for 1 h to obtain pretreated molybdenum disulfide nanosheets;
[0162] A2. Add 3 g of cerium nitrate to 25 mL of ethanol and 25 mL of deionized water, stir evenly, add 4 g of pretreated molybdenum disulfide nanosheets and 21.5 mL of 13 mol / L ammonia water, stir and react at 70 ° C for 3 h, cool to room temperature, take out, wash 3 times with ethanol, wash 3 times with deionized water, dry in an oven at 80 ° C for 30 min, calcine at 320 ° C for 3 h, cool to room temperature, and obtain modified molybdenum disulfide nanosheets;
[0163] A3. Add 4 g of 4,4'-dinonyl-2,2'-bipyridine to 55 mL of dichloromethane, stir evenly, add 7 g of modified molybdenum disulfide nanosheets, place on a rotary evaporator, stir at 200 rpm for 2 hours, heat in a 45°C water bath for 35 minutes, reduce pressure and evacuate to -0.05 MPa, filter, and dry in an oven at 50°C for 30 minutes to obtain a composite material.
[0164] Comparative Example 5
[0165] A method for preparing a water electrolysis hydrogen production catalyst with a high-efficiency mass transfer three-phase interface comprises the following preparation steps:
[0166] S1. The catalyst was mixed with the mixed acid, stirred at 55°C for 6h, filtered, and dried in an oven at 70°C for 10min to obtain a pretreated catalyst;
[0167] The ratio of catalyst to mixed acid is 10 g:70 mL;
[0168] The mixed acid is prepared by mixing an aqueous solution of sulfuric acid having a mass fraction of 80% and an aqueous solution of nitric acid having a mass fraction of 72% in a volume ratio of 50:20;
[0169] S2. The pretreated catalyst, polyethylene glycol and composite material were added to ethanol, stirred at 80°C for 40 min, ultrasonically treated at 60 KHz for 15 min, filtered, washed with deionized water 3 times, and dried in an oven at 70°C for 10 min to obtain a composite catalyst;
[0170] The ratio of pretreatment catalyst, polyethylene glycol, composite material and ethanol was 4 g:2 g:5 g:120 mL;
[0171] S3. Add the composite catalyst, cellulose and epichlorohydrin to ethanol, stir and react at 40°C for 30 minutes, continue stirring to form a gel, filter, wash with deionized water 3 times, and freeze-dry at -20°C for 2 hours to obtain a water electrolysis hydrogen production catalyst;
[0172] The dosage ratio of the composite catalyst, cellulose, epichlorohydrin and ethanol is 3g:5g:0.6mL:90mL.
[0173] The composite material is prepared by the following steps:
[0174] A1. 7 g of molybdenum disulfide nanosheets were added to 65 mL of deionized water, stirred evenly, and 2 g of zinc nitrate hexahydrate and 6 g of 2-methylimidazole were added. After stirring at 40 ° C for 3 h, the mixture was allowed to stand overnight, filtered, washed with deionized water 3 times, placed in 30 mL of tert-butanol to replace the water, taken out, and freeze-dried at -20 ° C for 1 h to obtain pretreated molybdenum disulfide nanosheets;
[0175] A2. Add 3 g of cerium nitrate to 25 mL of ethanol and 25 mL of deionized water, stir evenly, add 4 g of pretreated molybdenum disulfide nanosheets and 21.5 mL of 13 mol / L ammonia water, stir and react at 70 ° C for 3 h, cool to room temperature, take out, wash 3 times with ethanol, wash 3 times with deionized water, dry in an oven at 80 ° C for 30 min, calcine at 320 ° C for 3 h, cool to room temperature, and obtain modified molybdenum disulfide nanosheets;
[0176] A3. Add 4 g of 4,4'-dinonyl-2,2'-bipyridine to 55 mL of dichloromethane, stir evenly, add 7 g of modified molybdenum disulfide nanosheets, place on a rotary evaporator, stir at 200 rpm for 2 hours, heat in a 45°C water bath for 35 minutes, reduce pressure and evacuate to -0.05 MPa, filter, and dry in an oven at 50°C for 30 minutes to obtain a composite material.
[0177] The performance of the hydrogen production catalysts prepared by water electrolysis in Examples 1-3 and Comparative Examples 1-5 was tested.
[0178] 5 g of the above-prepared water electrolysis hydrogen production catalyst was added to 15 mL of ethanol and 20 mL of deionized water, and stirred evenly to obtain a slurry. The slurry was sprayed on the surface of a nickel mesh and dried naturally for 20 min to obtain a nickel mesh coated with the water electrolysis hydrogen production catalyst as a working electrode;
[0179] 1 mol / L KOH solution was added to deionized water as the electrolyte, a carbon rod was used as the counter electrode, saturated calomel was used as the reference electrode, and a nickel wire mesh coated with a catalyst for hydrogen production from electrolysis of water was used as the working electrode. Cyclic voltammetry was used for activation, and then linear sweep voltammetry was used for electrochemical performance tests of hydrogen evolution and oxygen evolution. The scanning speed was 2mV / s and the voltage was 1.8V to test the hydrogen production effect of the nickel wire mesh coated with the catalyst for hydrogen production from electrolysis of water;
[0180] The electrochemical active area (ECSA) of the nickel mesh coated with the water electrolysis hydrogen production catalyst at the initial stage and after 30,000 cycles was tested by cyclic voltammetry, with a scan rate of 50 mV / s; the current density of the water electrolysis hydrogen production catalyst at the initial stage and after 3000 cycles was tested by linear sweep voltammetry, with a rotation speed of 1600 rpm and a scan rate of 1 mV / s;
[0181] The test results are shown in Table 1 below.
[0182] Table 1 Performance test of hydrogen production catalysts prepared by electrolysis of water in Examples 1-3 and Comparative Examples 1-5
[0183]
[0184] It can be seen from the data in Table 1 that the water electrolysis hydrogen production catalysts prepared in Examples 1-3 have high catalytic activity. In Comparative Example 1, the pretreated molybdenum disulfide nanosheets were replaced with a composite material prepared from molybdenum disulfide nanosheets and added to the water electrolysis hydrogen production catalyst, and its catalytic performance decreased, proving that the porous structure of the zinc-based metal organic framework synthesized on the surface of the molybdenum disulfide nanosheets can increase the active sites of the water electrolysis hydrogen production catalyst and improve the catalytic reaction efficiency of the catalyst.
[0185] In Comparative Example 2, the modified molybdenum disulfide nanosheets were replaced with a composite material prepared by pretreated molybdenum disulfide nanosheets and added to the water electrolysis hydrogen production catalyst, and its catalytic performance decreased, indicating that nano-cerium oxide was formed on the surface of the pretreated molybdenum disulfide nanosheets, forming a concave-convex layer, which increased the contact area between the water electrolysis hydrogen production catalyst and the reactants, and nano-cerium oxide can promote the chemical reaction of hydrogen on the water electrolysis hydrogen production catalyst, thereby improving the catalytic hydrogen production efficiency of the water electrolysis hydrogen production catalyst.
[0186] The composite material prepared without adding 4,4'-dinonyl-2,2'-bipyridine in Comparative Example 3 was added to the water electrolysis hydrogen production catalyst, and its catalytic performance decreased, indicating that the nitrogen element contained in 4,4'-dinonyl-2,2'-bipyridine has good adsorption properties for platinum atoms, avoiding the precipitation of platinum atoms, resulting in a decrease in the catalytic performance of the water electrolysis hydrogen production catalyst, and 4,4'-dinonyl-2,2'-bipyridine is compounded to modify the porous material on the surface of the molybdenum disulfide nanosheet, thereby improving the adsorption capacity of platinum atoms.
[0187] In Comparative Example 4, dopamine-modified graphene oxide was replaced with a composite material prepared from graphene oxide and added to the water electrolysis hydrogen production catalyst, and its catalytic performance decreased, proving that dopamine-modified graphene oxide serves as a carrier of the pretreatment catalyst, increases the number of catalytic active sites, thereby improving the rate and efficiency of the catalytic reaction, and can effectively disperse the catalyst to prevent its agglomeration and deactivation.
[0188] In Comparative Example 5, the modified catalyst was replaced with a composite material prepared by a pretreated catalyst and added to the water electrolysis hydrogen production catalyst, and its catalytic performance decreased, proving that the modified catalyst and the composite material are stacked on each other to form a layered material, which provides more reaction sites and effectively reduces the activation energy of the hydrogen-oxygen reaction. The formed layered material can also adsorb and fix the platinum atoms that are displaced and detached from the catalyst during use, thereby avoiding the precipitation of platinum atoms and improving the catalytic activity of the water electrolysis hydrogen production catalyst.
[0189] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0190] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a water electrolysis hydrogen production catalyst with an efficient mass transfer three-phase interface, characterized in that: The method comprises the following preparation steps: S1. Mix the catalyst with the mixed acid, stir at 45-55 ° C for 4-6 hours, filter and dry to obtain a pretreated catalyst; S2. The pretreated catalyst and dopamine-modified graphene oxide were added to ethanol, stirred at 300-400 r / min for 20-30 min, filtered, washed, and dried to obtain a modified catalyst; S3. The modified catalyst, polyethylene glycol and the composite material are added to ethanol, stirred at 70-80 ° C for 30-40 min, ultrasonically treated at 40-60 KHz for 5-15 min, filtered, washed and dried to obtain a composite catalyst; S4. The composite catalyst, cellulose and cross-linking agent are added to the ethanol mixture, stirred at 30-40 ° C for 20-30 min, and freeze-dried to obtain a water electrolysis hydrogen production catalyst; The composite material is obtained by mixing modified molybdenum disulfide nanosheets and 4,4'-dinonyl-2,2'-bipyridine; The modified molybdenum disulfide nanosheet is obtained by mixing and reacting the molybdenum disulfide nanosheet with zinc nitrate hexahydrate and dimethylimidazole, and then mixing and reacting the molybdenum disulfide nanosheet with cerium nitrate and ammonia water.
2. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 1, characterized in that: The composite material is prepared by the following steps: A1. Add molybdenum disulfide nanosheets to deionized water, stir evenly, add zinc nitrate hexahydrate and 2-methylimidazole, stir and react at 30-40°C for 1-3h, let stand overnight, filter, wash, place in tert-butanol, stir, take out, and freeze-dry to obtain pretreated molybdenum disulfide nanosheets; A2. Add cerium nitrate to ethanol and deionized water, stir evenly, add pretreated molybdenum disulfide nanosheets and ammonia water, stir and react at 60-70 ° C for 2-3 hours, cool to room temperature, remove, wash, dry, calcine at 280-320 ° C for 1-3 hours, cool to room temperature to obtain modified molybdenum disulfide nanosheets; A3. Add 4,4'-dinonyl-2,2'-bipyridine to dichloromethane, stir evenly, add modified molybdenum disulfide nanosheets, stir at a speed of 100-200 rpm for 1-2 hours, heat at 35-45°C for 25-35 minutes, reduce pressure and evacuate, filter, and dry to obtain a composite material.
3. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 2, characterized in that: In step A1, the molybdenum disulfide nanosheets, deionized water, zinc nitrate hexahydrate and 2-methylimidazole are used in a ratio of (6-7) g: (55-65) mL: (1-2) g: (5-6) g.
4. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 2, characterized in that: In step A2, the ratio of cerium nitrate, ethanol, deionized water, pretreated molybdenum disulfide nanosheets and ammonia water is (2-3) g: (15-25) mL: (15-25) mL: (3-4) g: (1-2) mL.
5. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 2, characterized in that: In step A3, the ratio of the amount of 4,4'-dinonyl-2,2'-bipyridine, dichloromethane and modified molybdenum disulfide nanosheets is (2-3) g: (45-55) mL: (5-7) g.
6. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 1, characterized in that: In step S1, the ratio of the catalyst to the mixed acid is (8-10) g:(60-70) mL; the mixed acid is prepared by mixing an aqueous sulfuric acid solution and an aqueous nitric acid solution in a volume ratio of (40-50):(10-20).
7. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 1, characterized in that: In step S2, the ratio of the pretreatment catalyst, dopamine-modified graphene oxide and ethanol is (2.3-2.5) g: (3.2-3.4) g: (45-55) mL.
8. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 1, characterized in that: In step S3, the ratio of the modified catalyst, polyethylene glycol, composite material and ethanol is (3-4) g: (1-2) g: (4-5) g: (80-120) mL.
9. The method for preparing a water electrolysis hydrogen production catalyst having a high-efficiency mass transfer three-phase interface according to claim 1, characterized in that: In step S4, the ratio of the composite catalyst, cellulose, cross-linking agent and ethanol is (2-3) g: (4-5) g: (0.4-0.6) mL: (70-90) mL.
Citation Information
Patent Citations
Nitrogen doping carbonized bacterial cellulose / graphene / platinum composite nanomaterial and preparation method thereof
CN106410223A
Preparation method and application of Pt / rGO / PDA@NF composite material
CN111490255A
Cerium-modified molybdenum disulfide bifunctional catalyst as well as preparation and application thereof
CN115584530A
Platinum complex, manufacturing method thereof and platinum catalyst constructed thereby
US20110177937A1